ANALISIS PEMASARAN PADA INDUSTRI RUMAH TANGGA PENGOLAHAN KERIPIK UBI - Asnamawati, Lina; Nurmalia, Ana (University of Prof. Dr. Hazairin, SH, 2024)
The cassava processing industry in Pasar Pedati Village, Pondok Kelapa District, Central Bengkulu Regency, is part of the agro-industrial sector with significant potential but still faces several challenges. Despite the presence of several craftsmen producing cassava chips, most operate on a household scale and encounter limitations in marketing and product value-added. These constraints include limited access to cassava raw materials and increasingly tight market competition. Therefore, this study aims to analyze marketing in the household cassava chips processing industry in the village. The research method used a purposive approach with a population of 20 cassava chip craftsmen, all of whom were respondents using a census method. Descriptive analysis was employed to analyze marketing channels, while for marketing margins, the research results revealed that the average marketing margin received by respondents was Rp. 850, with a selling price of Rp. 5,000 per packet, enabling craftsmen to sell 2,509 packets per month. A significant marketing margin will also bring substantial profits to producers regarding the processed cassava chip products. With sufficiently large marketing margins generated by each craftsman, all respondents consider cassava chip processing as their primary household business.